PALMITIC AND OLEIC ACIDS AND THEIR ROLE IN PATHOGENESIS OF ATHEROSCLEROSIS - V. N. Titov; A. M. Dygai; M. Yu. Kotlovskiy; Ye. V. Kurdoyak; A. V. Yakimenko; I. Yu. Yakimovich; N. V. Aksyutina; Yu. V. Kotlovskiy (Бюллетень сибирской медицины)
On the basis of phylogenetic theory of general pathology, the cause of a noninfectious disease whose occurrence in a population is more than 5–7% is an impaired biological function or reaction to the environment. From the general biology viewpoint, high mortality rate related to cardio-vascular diseases and atherosclerosis (intercellular deficiency of polyenic fatty acids (PFA)) is just extinction of the Homo sapiens population upon adaptation to new environmental factors. The biological function of throphology (feeding) and biological reaction of exotrophy (external feeding) are impaired in several aspects, the major of which is nonphysiologically high dietary content of saturated fatty acids, primarily, of palmitic fatty acid (FA). The lipoprotein system formed at early stages of phylogenesis cannot transport and provide physiological deposition of great amounts of palmitic FA, which leads to the development of an adaption (compensatory) and accumulation disease. This results in hypermipidemia, impaired bioavailability of PFA to cells, compesatory production of humoral mediators from ω-9 eicosatrienoic mead FA, disorders in physiological parameters of cell plasma membrane and integral proteins, nonphysiological conformation of apoВ-100 in lipoproteins, formation of ligandless lipoproteins (biological litter) and impairments in the biological function of endoecology, utilization of ligandless lipoproteins in arterial intima by phylogenetically early macrophages that do not hydrolyze polyenic cholesterol esters, increase in the intensity of the biological reaction of inflammation, and destructive and inflammatory lesions in arterial intima of an atheromatosis or atherothrombosis type. Atheromatous masses are catabolites of PFA which were not internalized by phylogenetically late cells via receptor-mediated pathway.